The Souls of White Folk : African American Writers Theorize Whiteness - Watson, Veronica T. (Book collections on Project MUSE., 2013)
This study considers the substantial body of African American writing that critiques whiteness as social construction and racial identity. Arguing against the prevailing approach to these texts that says African American writers retreated from issues of "race" when they wrote about whiteness, the author instead identifies this body of literature as an African American intellectual and literary tradition that she names "the literature of white estrangement." In chapters that theorize white double consciousness (W. E. B. Du Bois and Charles Chesnutt), white womanhood and class identity (Zora Neale Hurston and Frank Yerby), and the socio-spatial subjectivity of southern whites during the civil rights era (Melba Patillo Beals), the author explores the historically situated theories and analyses of whiteness provided by the literature of white estrangement from the late nineteenth through the mid-twentieth centuries.